The Offspring Number of Drosophila melanogaster Meigen Consuming Monosodium Glutamate for Two Generations - Atika, Anggun Risma; Fauzi, Ahmad (Proceedings of the International Conference on Green Technology; Vol 8 No 1 (2017): Proceedings of the International Conference on Green Technology, 2017)
Monosodium Glutamate (MSG) is one of the flavor enhancers that most commonly used in various foods but its safety is still in doubt. In this research, a study was conducted to examine the effects of MSG administration on offspring number of Drosophila melanogaster for two generations. D. melanogaster ♂ wild-type strain was crossed with ♀ wild-type strain in glass bottle were fed with two different concentrations of 2.0% and 2.5% of MSG. Along with treated, the control flies were also set up without MSG. Based on ANOVA result, F count concentration variable on offspring number was 25.159 with the p-value 0.000 < 0.05 and F count generation variable on offspring number was 14.095 with the p-value 0.001 < 0.05. Administration of 2.0% MSG caused the increasing of offspring number but at 2.5% level, MSG caused the decreasing of offspring number. Furthermore, first-generation had a significantly higher offspring number than the second generation. The result indicated there was an accumulation of negative impacts of MSG consumption in the second generation.